2016
DOI: 10.1074/jbc.m115.681122
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane Protein 184A Is a Receptor Required for Vascular Smooth Muscle Cell Responses to Heparin

Abstract: Vascular cell responses to exogenous heparin have been documented to include decreased vascular smooth muscle cell proliferation following decreased ERK pathway signaling. However, the molecular mechanism(s) by which heparin interacts with cells to induce those responses has remained unclear. Previously characterized monoclonal antibodies that block heparin binding to vascular cells have been found to mimic heparin effects. In this study, those antibodies were employed to isolate a heparin binding protein. MAL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 43 publications
6
44
0
Order By: Relevance
“…The observations that pretreatment with antibodies to a putative heparin receptor decreases TNF␣-induced JNK and p38 activation and decreases stress fiber formation are consistent with previous reports showing that these antibodies mimic the effects of heparin in VSMCs (19,22,24). Here we provide functional evidence that the anti-inflammatory effects of heparin in ECs are mediated through the heparin receptor TMEM184A, as seen in VSMCs (28). TMEM184A knockdown interferes with heparin responses, confirming our HRmAb evidence.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The observations that pretreatment with antibodies to a putative heparin receptor decreases TNF␣-induced JNK and p38 activation and decreases stress fiber formation are consistent with previous reports showing that these antibodies mimic the effects of heparin in VSMCs (19,22,24). Here we provide functional evidence that the anti-inflammatory effects of heparin in ECs are mediated through the heparin receptor TMEM184A, as seen in VSMCs (28). TMEM184A knockdown interferes with heparin responses, confirming our HRmAb evidence.…”
Section: Discussionsupporting
confidence: 92%
“…VSMCs eliminated heparin responses (28). To determine whether this heparin-responsive protein identified with our HRmAbs and confirmed in VSMC is also responsible for the heparin effects in ECs reported here, we first confirmed that TMEM184A is present in RAOECs across the range of cell density we studied (Fig.…”
Section: Dusp1 Is Critical For Heparin-induced Decreases In Jnk and P38supporting
confidence: 57%
See 3 more Smart Citations